UNCCANY AND GROTTESQUE ASPECTS IN FEMALE CHARACTERS IN ADELICE SOUZA - Suelen Gonçalves Vasconcelos (Travessias, 2012)
Adelice Souza is a short story writer and playwright from Bahia whose writing presents strength through the creation of different female characters. In the short stories, A atriz que no sabia morrer and A mulher nua, the author breaks away from the model shown by local color writers of the typical baiana woman including stereotypes such as the macho, sensual, submissive, crying or religious woman. Adelice Souzas narratives show uncanny women in grotesque situations as an attempt to escape from a pattern of female representations marked by belonging to something socially accepted or idealized. Souza creates strange, grotesque, independent lonely women characteristics used to highlight these characters peculiarity far from the known stereotypes. In the chosen short stories the grotesque situation of a woman representing the role of a dog and a strange hand which possesses a female body are examples of situations which bring these women to light detaching them from common female paradigms. The female body is constructed as something different through the use of the uncanny and the grotesque which may be seem as strategies to represent a different way of being in disconformity with ruling stereotypes.